The effects of PSA kinetics on the outcome of hypofractionated salvage radiotherapy for biochemical recurrence of prostate cancer after prostatectomy. (5th September 2020) - Ishikawa, Hitoshi; Higuchi, Keiko; Kaminuma, Takuya; Takezawa, Yutaka; Saito, Yoshitaka; Etsunaga, Toru; Maruo, Kazushi; Kawamura, Hidemasa; Kubo, Nobuteru; Nakano, Takashi; Kobayashi, Mikio
Abstract: The feasibility and efficacy of hypofractionated salvage radiotherapy (HS-RT) for prostate cancer (PC) with biochemical recurrence (BR) after prostatectomy, and the usefulness of prostate-specific antigen (PSA) kinetics as a predictor of BR, were evaluated in 38 patients who received HS-RT without androgen deprivation therapy between May 2009 and January 2017. Their median age, PSA level and PSA doubling time (PSA-DT) at the start of HS-RT were 68 (53–74) years, 0.28 (0.20–0.79) ng/ml and 7.7 (2.3–38.5) months, respectively. A total dose of 60 Gy in 20 fractions (three times a week) was three-dimensionally delivered to the prostate bed. After a median follow-up of 62 (30–100) months, 19 (50%) patients developed a second BR after HS-RT, but only 1 patient died before the last follow-up. The 5-year overall survival and BR-free survival rates were 97.1 and 47.4%, respectively. Late grade 2 gastrointestinal and genitourinary morbidities were observed in 0 and 5 (13%) patients, respectively. The PSA level as well as pathological T-stage and surgical margin status were regarded as significant predictive factors for a second BR by multivariate analysis. BR developed within 6 months after HS-RT in 11 (85%) of 13 patients with a PSA-DT < 10 months compared with 1 (17%) of 6 with a PSA-DT ≥ 10 months (median time to BR: 3 vs 14 months, P  < 0.05). Despite the small number of patients, our HS-RT protocol seems feasible, and PSA kinetics may be useful for predicting the risk of BR and determining the appropriate follow-up schedule.